Maine’s Workers’ Compensation System: Is it Making the Grade? - Reitman, Jonathan (Maine Policy Review, 1996)
Fundamental changes in Maine’s workers’ compensation system were legislated four years ago. What impact have they had and what remains on the policy agenda? This article provides a comprehensive and balanced assessment of that reform effort, suggesting dramatic improvements in the system. But work remains: Vocational rehabilitation, labor-management collaboration, and cost-containment are especially in need of improvement.